Implementasi Projek Penguatan Profil Pelajar Pancasila Melalui Pelatihan Pembuatan Lilin Aromaterapi Bagi Guru di SDN Karang Mekar 1 Banjarmasin - Tika Puspita Widya Rini; Ali Rachman; Arta Mulya Budi Harsono; Aldy Ferdiyansyah; Ari Hidayat; M. Ziyan Takhqiqi Arsyad (Journal of Innovative and Creativity, 2026)
Developing a project to strengthen the Pancasila student profile is an effective strategy for teachers to improve the quality of learning through innovative activities relevant to the challenges and demands of modern developments. However, the implementation of the project at SDN Karang Mekar 1 Banjarmasin, a partner school, still faces limitations, such as limited teacher knowledge and skills in developing innovative and economically valuable projects. This community service activity aims to improve teacher professionalism in implementing the project to strengthen the Pancasila student profile through aromatherapy candle-making training at SDN Karang Mekar 1 Banjarmasin. The activity was implemented through five stages of community service: outreach, training, technology application, mentoring and evaluation, and program sustainability. The aromatherapy candle-making training has demonstrated significant results. This activity successfully improved teachers' understanding of project-based learning, as evidenced by improved post-test scores compared to pre-test scores. Furthermore, teachers' active listening, note-taking, practice, and discussion during the training were also positive. These results indicate that the training has been effective in improving teachers' competency in implementing the Pancasila student profile project, which is expected to improve the quality of learning at the school.